Hizbut Tahrir's View on Usury and Its Implications in Fiqh Muamalah Education - Ramadhani, Hanifa; Maksum, Muh. Nur Rochim (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Usury is one of the fundamental issues in fiqh muamalah that has a broad impact on the economic life of individuals and society. The development of a modern economic system dominated by interest-based capitalism has made the practice of usury increasingly complex and structured, giving rise to diverse views among Islamic scholars and organizations. Hizbut Tahrir is an Islamic movement that takes a firm stance against usury, viewing it as a practice that is absolutely forbidden and an integral part of the capitalist economic system that contradicts Islamic teachings. This article aims to analyze Hizbut Tahrir's views on usury and its implications for fiqh muamalah education. This study uses a qualitative paradigm with a library research method. Primary data sources include the book Sistem Ekonomi Islam (Islamic Economic System) by Taqiyuddin an-Nabhani and Hizbut Tahrir's tsaqofah literature, while secondary data sources come from scientific journals and articles relevant to the theme of usury and fiqh muamalah education. Data collection techniques were carried out through searching, reading, and in-depth analysis of relevant texts. The results of the study show that Hizbut Tahrir views usury not only as a violation of muamalah law at the individual level, but also as a systemic problem that is the main pillar of the capitalist economy. Therefore, according to Hizbut Tahrir, the elimination of usury cannot be done partially, but requires the implementation of an Islamic economic system as a whole. This view has direct implications for fiqh muamalah education, which is directed not only at understanding transaction laws, but also at forming ideological awareness, critical attitudes towards modern economic practices, and understanding the relationship between muamalah law and the economic system. Fiqh muamalah education in the perspective of Hizbut Tahrir is positioned as an instrument for guiding individuals and society to reject usurious practices and encourage the realization of an Islamic economic system. Thus, this study confirms that Hizbut Tahrir's view of usury shapes the orientation of fiqh muamalah education to be normative, critical, and transformative.